Friends or foes? A theoretical approach towards constructivism, realism and students’ wellbeing via academic literacy practices - Eybers, O.O. (South African Journal of Higher Education, 2018)
The following theoretical analysis aimed to highlight perceived, conceptual differences between constructivist and realist ontologies as meta-theories for understanding students’ well-being in institutions of higher learning; specifically, in relation to how first-year students attempt to master academic literacy practices. This theoretical investigation aimed to determine if the two ontologies are theoretically compatible in research endeavours which are geared towards understanding the wellness of first-year students as they attempt to demonstrate mastery of academic literacy practices. The central method applied in this conceptual probe was an interpretive and textual focus on key, local and international perspectives towards student well-being in higher education. In addition, the study aimed to conceptually expound constructivist and realist schools of thought as modal frameworks for understanding student learning experiences, including their well-being as novice members of our academies. The outcome of the investigation revealed that while the two ontologies presented theoretical and conceptual divergences towards approaching first-year, students’ well-being as they attempt to master academic literacy practices; mainly, a view of being or reality as mind-emergent or mind-independent, both constructivism and realism are applicable ontologies for comprehending this very phenomenon. This analytical probing concluded by asserting that while constructivism and realism are distinct meta-theories towards understanding the lived experiences and well-being of first-year students engaging in academic literacy practices, they need not be perceived as theoretical foes. Both ontologies are applicable, conceptual frameworks for illustrating how, at individual and interactive levels with significant others, the well-being of students may be approached as they attempt to demonstrate competence in conventions associated with academic literacy.